Designing a Company Profile as Promotional Media at Zaeni Convection Using WordPress - Taruna, Sumadanu Budi; Rini Suwartika (Politeknik Piksi Ganesha Indonesia, 2023)
In this digital era, business actors need to digitize their companies. One way to digitize is by creating a company profile website that could improve communication between clients and business actors. This research aim is to make a company profile website design at Zaeni Convection using WordPress. Zaeni Convection is a company engaged in the clothing industry. From the older research, Zaeni Convection needs a platform as a promotional medium for their company. In this study, the authors used the SDLC or Software Development Lifecycle method as a design to build a company profile website. In this study, 21 people filled out a questionnaire resulting that with the company profile website, promotional media became more efficient. The results of this study are a company profile website that can help companies promote their products and company profiles as well as company services.